2021
DOI: 10.1101/2021.04.29.442061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decitabine Reactivation of FoxM1-Dependent Endothelial Regeneration and Vascular Repair for Potential Treatment of Elderly ARDS and COVID-19 Patients

Abstract: Aging is a major risk factor of high incidence and increased mortality of acute respiratory distress syndrome (ARDS) and COVID-19. We repot that aging impairs the intrinsic FoxM1-dependent endothelial regeneration and vascular repair program and causes persistent lung injury and high mortality following sepsis. Therapeutic gene transduction of FOXM1 in vascular endothelium or treatment with FDA-approved drug Decitabine was sufficient to reactivate FoxM1-dependent lung endothelial regeneration in aged mice, rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…We also demonstrated GCN2 activation in MCT-induced rat PAH model and in IPAH patients. Employing endothelium-targeted nanoparticles to deliver the CRISPR/Cas9 system 35,50 to knockout Gcn2 selectively in ECs, we also observed attenuated PH in these ECspecific knockout mice, demonstrating the important role of hypoxia-activated GCN2 in ECs in mediating pulmonary vascular remodeling and pulmonary hypertension development. Since we also observed GCN2 hyperphosphorylation in pulmonary vascular SMCs and interstitial tissues in MCT rats and IPAH patients, it is possible that GCN2 can also be activated by other PAHcausing factors such as growth factors or inflammatory mediators 51 EDN1, an EC-derived factor, plays an important role in the pathogenesis of PAH in increasing vasoconstriction and cell proliferation.…”
Section: Discussionmentioning
confidence: 71%
“…We also demonstrated GCN2 activation in MCT-induced rat PAH model and in IPAH patients. Employing endothelium-targeted nanoparticles to deliver the CRISPR/Cas9 system 35,50 to knockout Gcn2 selectively in ECs, we also observed attenuated PH in these ECspecific knockout mice, demonstrating the important role of hypoxia-activated GCN2 in ECs in mediating pulmonary vascular remodeling and pulmonary hypertension development. Since we also observed GCN2 hyperphosphorylation in pulmonary vascular SMCs and interstitial tissues in MCT rats and IPAH patients, it is possible that GCN2 can also be activated by other PAHcausing factors such as growth factors or inflammatory mediators 51 EDN1, an EC-derived factor, plays an important role in the pathogenesis of PAH in increasing vasoconstriction and cell proliferation.…”
Section: Discussionmentioning
confidence: 71%
“…It is highly expressed in the PBMCs of COVID-19 patients [ 45 ]. Studies have shown that the expression of CCNB1 markedly increases during the recovery period of patients, which is related to the endothelial regeneration and vascular repair during the recovery process of ARDS; therefore, CCNB1 may have different expression levels in patients with different states of ARDS [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19 studies, CMPK2 was highly upregulated in severe cases related to ARDS [202,203]. Moreover, FOXM1-dependent tissue regeneration is impaired in severe COVID-19 cases, causing sustained lung injury and a high fatality rate [204]. RRM2, a cell cycle regulator, had an increased expression in lung adenocarcinoma with a poor prognosis [205].…”
Section: Important Immune-related Proteins With the Ranking Scoresmentioning
confidence: 99%
“…Decitabine is a pyrimidine nucleoside antimetabolite used to treat myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) [222,223]. A study in the mice model showed that decitabine improved FOXM1-dependent endothelial regeneration and vascular repair [204]. As mentioned above, lung tissue degeneration can cause worsening lung injury.…”
Section: Potential Drugs To Cure Severe Covid-19 Patientsmentioning
confidence: 99%